ANALISIS MAQĀṢID AL-SYARĪʿAH TERHADAP KONTINUITAS TRADISI SIPALISUNNA DI MASYARAKAT BUGIS - S, Samsidar; Bakry, Muammar; Amin, Abd. Rauf; Makkarateng, Ma'adul Yaqien; Syam, Anna Rahma (Program Studi Hukum Keluarga Fakultas Syariah UIN Datokarama Palu, 2025)
This article discusses the value of maqāṣid al-syarī'ah in the practice of sipalisunna marriage, namely marriage with close relatives, in the context of Bugis society. Sipalisunna marriage has a depth of meaning that goes beyond mere social ties, because it contains fundamental sharia objectives. Through the lens of maqāṣid al-syarī'ah, this marriage aims to preserve offspring, maintain family honor, and strengthen social relations between relatives. This research uses a qualitative approach with dialogue to understand the practice of sipalisunna marriage in Bugis society. The findings show that despite the negative stigma associated with marriage to close relatives, the Bugis community continues to carry out this tradition by considering the values ​​of family unity and social solidarity. In addition, this article highlights the importance of understanding maqāṣid al-sharī'ah in assessing the positive and negative impacts of this practice on society. Thus, this article contributes to the development of thinking about the synergy between local traditions and sharia principles. Emphasis on the value of maqāṣid al-syarī'ah in sipalisunna marriages can help people to better understand and face modern challenges without ignoring the existing cultural heritage. This is expected to strengthen cultural identity while maintaining social harmony in Bugis society